Contemporary Trends in Oral Anticoagulant Prescription in Atrial Fibrillation Patients at Low to Moderate Risk of Stroke After Guideline-Recommended Change in Use of the CHADS2 to the CHA2DS2-VASc Score for Thromboembolic Risk Assessment: Analysis From the National Cardiovascular Data Registry's Outpatient Practice Innovation and Clinical Excellence Atrial Fibrillation Registry. Issue 5 (May 2017) - Katz, David F.; Maddox, Thomas M.; Turakhia, Mintu; Gehi, Anil; O'Brien, Emily C.; Lubitz, Steven A.; Turchin, Alexander; Doros, Gheorghe; Lei, Lanyu; Varosy, Paul; Marzec, Lucas; Hsu, Jonathan C.
Abstract : Background—: Use of the CHA2 DS2 -VASc score instead of the CHADS2 score for thromboembolic risk stratification and initiation of oral anticoagulation (OAC) was recommended in the 2014 American Heart Association/American College of Cardiology/Heart Rhythm Society atrial fibrillation (AF) guidelines. We sought to define the proportion of patients with AF qualifying for and receiving OAC in contemporary practice by applying the CHA2 DS2 -VASc score to patients with a low CHADS2 score. Methods and Results—: Among patients with AF enrolled in the American College of Cardiology National Cardiovascular Data Registry's outpatient Practice Innovation and Clinical Excellence registry (2008–2014) CHADS2 score of 0 or 1, we calculated the impact of adoption of the CHA2 DS2 -VASc score on the proportion of patients with an indication for OAC. We examined trends in prescription of OAC overall, direct OAC (dabigatran/rivaroxaban/apixaban), and multivariable associations between clinical characteristics and OAC use. Of 346 068 patients with AF aged 65±12 years, 61% were men and 65% were white. In total, 24% of those with CHADS2 =0 and 81% of those with a CHADS2 =1 were reclassified as having a definite indication for OAC (CHA2 DS2 -VASc score ≥2). OAC use increased from 37% to 48% during the study period, and direct OAC use increased from 5% to 30%. Increasing CHA2 DS2 -VASc score (odds ratio, 2.07; 95% confidence interval, 1.97–2.19 for score of 4 versus 0) and rhythm control strategy (odds ratio, 1.34; 95% confidence interval, 1.30–1.39) were associated with increased OAC use. Conclusions—: Adoption of the CHA2 DS2 -VASc score reclassifies 64.5% of patients with AF with low CHADS2 scores into a class I indication for OAC prescription. Overall OAC prescription increased between 2011 and 2014. Abstract : Supplemental Digital Content is available in the text.